أثر الإدارة المركزية واللامركزية في إدارة العاملين وتطوير الإنتاج في شركاتنا المنتجة - زريقة, يسرى; إبراهيم, أحمد شيخ (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
تؤدي الإدارة الناجحة دوراً مهماً ومميزاً في حياة المجتمعات البشرية من خلال تأثيرها المباشر على مؤسسات التنمية البشرية الاقتصادية والاجتماعية والتربوية والتعليمية, وقدرتها على إحداث تغيرات جذرية في هذه المؤسسات ونقلها من حالة سكون وركود إلى حالة ديناميكية فاعلة ومؤثرة, تؤسس لبناء مادي تحتي يعكس البنى الفوقية في المجتمع كالثقافة والتعليم والدين والأخلاق.ولهذا السبب فإنّ معظم البلدان المهتمة بعملية التنمية الشاملة في مجتمعاتها تولي أهمية كبيرة لتطوير أساليب الإدارة بجوانبها المركزية واللامركزية ـ ويهدف هذا البحث إلى الكشف عن دور الإدارة الناجحةـ المركزية منها واللامركزية في تطور أداء العاملين في شركاتهم وفي تطوير إنتاج هذه الشركات ـ والوقوف عند الإدارة الأمثل((المركزية أو اللامركزية)) وتعميم النموذج الأفضل بما يخدم مسألة التنمية الشاملة في بلدنا والتي نحن أحوج ما نكون إليها لتطوير بلدنا في ميادين التنمية كافة, بما يحقق لنا((تنمية مستدامة)) ـThe successful management an important and essential role in the life of human societies through its direct influence on all human, economic, social and educational development institutions, and its ability in instilling radical changes in these institutions and move them from stillness and recession into a dynamic active state that establishes a materialistic infra structure that reflects the supra-structure such as education, teaching, religion and ethics.For this reason, all the interested countries in development process pay great attention to develop management methods in its central and non-central aspects. In this research will we focus on the role of a successful the central and non-central administration in developing the staff performance in their companies and in developing the production of these companies, and study the central and non-central administration and generalize the best model that serves the matter of the overall development in our country which we need to develop our country in all aspects of overall development s we can achieve an ongoing development.